Data for "Diversity, biogeography, and evolution of European freshwater gastropods through time: a voyage across scales" - Neubauer, Thomas A.; Justus Liebig University Giessen (My University, 2023)
The dataset contains the taxonomic, geographic, and stratigraphic data on freshwater mollusks used in the habilitation thesis of T. A. Neubauer at JLU (2023). The dataset is divided into four parts: 1. species occurrence data for fossil European and North American freshwater gastropods from the Triassic to the Pleistocene. This includes information on geography, taxonomy/systematics, stratigraphy, and literature sources. The information was acquired over the past 10 years from the primary literature and constantly updated. Parts were published in previous papers by the author. 2. A species list of all fossil and extant fresh- and brackish-water Mollusca stored in the online database MolluscaBase (https://molluscabase.org/), as of 3 January 2023. 3. Distribution data in the form of geographic polygon names for all taxa in (2), as of 19 December 2022. 4. Fossil age data for all taxa in (2), as of 19 December 2022. Disclaimer: Data from MolluscaBase are used and stored with kind permission. MolluscaBase and its parent, the World Register of Marine Species (WoRMS, https://www.marinespecies.org/), is constantly updated and thus contain the most recent available information on the species and associated distribution and age information.
Keywords: Biodiversity; Freshwater; Gastropoda; Paleobiology; Diversification; Biogeography; ddc:560; ddc:570